Workshop peningkatan kemampuan guru menulis rencana penelitian tindakan kelas di Kecamatan Minas Kabupaten Siak - Yenita Roza; Sehatta Saragih (Unri Conference Series: Community Engagement, 2019)
Classroom Action Research (CAR) is one form of research that is recommended to be carried out by teachers in developing capacity as a professional teacher. Through this research the teacher at the same time improves the quality of learning carried out in the classroom, so that this is used as one of the conditions in proposing teacher promotion. From interviews and observations in Minas Subdistrict, Siak Regency, there were many teachers who were constrained for promotion because of their ability to conduct class action research is low. The program done aims to assist the teacher in writing Class Action Research (CAR) plans so that they are ready to do the research. The target community of the activity is 30 junior high school teachers with varied working experience ranging from 4-15 years. The activities were carried out through workshops conducted in five stages, namely debriefing about action research, mentoring of research plan writing, research plan discussion, revision of research plans and presenting of research plan. The results of the service showed that the workshop activities had a positive impact on the ability of participants to develop CAR plans. The average achievement of participants in scale 4 is 2.53 in the good category.